CLOUD ACCOUNTING AS A NEW BUSINESS MODEL - Chikkala, Ramya; Jaffer, Dr Syed (The journal of contemporary issues in business and government, 2022)
Earlier Information Technology (IT) is considered to be a separate department which is primarily dealing with coding for business applications, website designs, etc. Now, IT is now an integral part of every department and accounting is no exception. Adapting IT concepts such as Artificial Intelligence, Robotics, automation, cloud technology, etc. has changed the way of doing business. Electronic data processing brings in greater efficiency and adds value to the business. Various business reports can be easily and quickly prepared with help of these computer systems. Increased functionality, improved accuracy, faster data processing, better external reporting, processing and presenting real-time data, etc. are few benefits of adopting electronic data processing in business. Cloud accounting is the most popular technological advancement in the field of accountancy. Cloud accounting enables bookkeepers and accountants to work on the same system irrespective of the location. It brings proficiency in bookkeeping and streamlines financial administration in any organization and helps in providing real-time data to business stakeholders. Cloud is a network model where data is stored in centralized servers and can be accessed anywhere with internet-enabled devices. The recent Covid pandemic has pushed all organizations around the world, to make remote working easier to their employees. Organizations with less manpower are also adopting cloud accounting software to handle and process their financial data. This paper has attempted to provide an overview of the concept of cloud accounting, the need for cloud accounting, and the benefits and risks associated with it.